ANALYSIS ON PERFORMANCE COMPARISON BETWEEN CRYPTOCURRENCY INDEX 30, LQ45 INDEX AND GOLD AS ALTERNATIVE INVESTMENT - Putra Sulaeman, Nashrullah
The financial crisis in 2008 caused a group of anonymous named Satoshi Nakamoto to create a cryptocurrency program called Bitcoin as one of the main currency solutions that is not tied to the central bank. To date, there have been more than 2000 crypto currencies recorded on coinmarketcap.com. Crypto currencies can also be used as investment instruments, as evidenced by the rise in the crypto currency market by thousands of percent over the past 5 years. The analysis was carried out to measure the performance of the diversified cryptocurrency index; CCI30 and compare it with traditional investment instruments such as shares, which are represented by LQ45 and Gold. Judging from the risk factors, rate of return, and evaluation using the Sharpe ratio, Crypto currency can outperform LQ45 and Gold. However, the risk that is behind the crypto assets is very large making it only suitable for short-term investments and is only best used by investors with aggressive risk profiles. Using excel solver tools, the optimal proportion of the portfolio containing these three assets is 19.89% CCI30, 34.09% LQ45, and 46.02% Gold with a potential Sharpe ratio of a maximum of 2325.87%. The best investment strategy using optimal proportions is semiannual rebalancing with a total return of 3623.48%.